Clinical implications of gastric complications on levodopa treatment in Parkinson's disease. (July 2020) - Pfeiffer, Ronald F.; Isaacson, Stuart H.; Pahwa, Rajesh
Abstract: Disorders of the gastrointestinal (GI) tract are common and distressing nonmotor symptoms of Parkinson's disease (PD) that can adversely affect levodopa absorption and lead to OFF periods, also known as motor fluctuations. Gastroparesis, which is primarily defined as delayed gastric emptying (DGE), and Helicobacter pylori infection, which is present with increased frequency in PD, are among the most common and important GI disorders reported in PD that may impair oral levodopa absorption and increase OFF time. Symptoms of gastroparesis include nausea, vomiting, postprandial bloating, fullness, early satiety, abdominal pain, and weight loss. DGE has been reported in a substantial fraction of individuals with PD. Symptoms of H. pylori infection include gastritis and peptic ulcers. Studies have found that DGE and H. pylori infection are correlated with delayed peak levodopa plasma levels and increased incidence of motor fluctuations. Therapeutic strategies devised to minimize the potential that gastric complications will impair oral levodopa absorption and efficacy in PD patients include treatments that circumvent the GI tract, such as apomorphine injection, levodopa intestinal gel delivery, levodopa inhalation powder, and deep brain stimulation. Other strategies aim at improving gastric emptying in PD patients, primarily including prokinetic agents. Highlights: Gastric complications such as gastroparesis are common in Parkinson's disease. Gastroparesis and Helicobacter pylori infection may impair oral levodopa absorption. Inconsistent levodopa absorption leads to motor fluctuations and OFF periods. Gastric complications are associated with OFF periods. Non-oral levodopa and gastroparesis therapies may decrease OFF periods.